2013
DOI: 10.1002/anie.201305574
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium(III) Spin Labels for High‐Sensitivity Distance Measurements in Transmembrane Helices

Abstract: Distance determination, by pulse EPR techniques, between two spin labels attached to biomolecules has become an attractive methodology to probe conformations and assemblies of biomolecules in frozen solutions. [1][2][3] Among these techniques, double electron-electron resonance (DEER or PELDOR), [4,5] which can access distances in the range of 1.7 to 8 nm, is highly popular, [6][7][8] and the most widely used spin labels are nitroxide radicals. Membrane proteins in their natural environment are of particular i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
58
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 32 publications
2
58
0
Order By: Relevance
“…Modifications of this approach involve the use of non-identical spin labels, in particular a Gd(III) center and a nitroxide [3,4], as well as different experimental schemes, such as relaxation-induced dipolar modulation (RIDME) [5] or continuous-wave EPR [6]. Distance measurements involving Gd spin labels have been successfully demonstrated on a number of systems, including model compounds, peptides, nanoparticles, proteins and DNAs [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Moreover, a promising biochemical property of Gd spin labels is the stability under reducing conditions, which recently enabled Gd-Gd distance measurements of peptides and proteins embedded in cellular environments [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Modifications of this approach involve the use of non-identical spin labels, in particular a Gd(III) center and a nitroxide [3,4], as well as different experimental schemes, such as relaxation-induced dipolar modulation (RIDME) [5] or continuous-wave EPR [6]. Distance measurements involving Gd spin labels have been successfully demonstrated on a number of systems, including model compounds, peptides, nanoparticles, proteins and DNAs [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Moreover, a promising biochemical property of Gd spin labels is the stability under reducing conditions, which recently enabled Gd-Gd distance measurements of peptides and proteins embedded in cellular environments [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…-Gd 3? PELDOR distance measurements, simultaneous two-site attachment is required and has been established using chemical tags (Raitsimring et al 2007;Potapov et al 2010;Gordon-Grossman et al 2011;Lueders et al 2011;Song et al 2011;Yagi et al 2011;Garbuio et al 2013;Matalon et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work in a diverse collection of systems (Kaminker et al, 2012;Lueders et al, 2011;Matalon et al, 2013a;Song et al, 2011;Yulikov et al, 2012) has demonstrated that Gd 3+ offers many advantages as an alternative spin label for high-field DEER measurements (Goldfarb, 2012(Goldfarb, , 2014Potapov et al, 2010b;Raitsimring et al, 2007;Yagi et al, 2011). This manuscript extends the capabilities of Gd 3+ to include accurately resolving distances between multiple neighboring proteins within a membrane protein oligomer by leveraging the reduction of multispin effects.…”
Section: Introductionmentioning
confidence: 91%